Hubungan tingkat stres dengan munculnya perilaku bullying pada siswa SMP - Hilda, Hilda Meilinda Safitri (JOURNAL OF Mental Health Concerns, 2024)
Abstract   Background: The city of Bandar Lampung is the city/district that ranks second with the most cases of violence occurring among junior high school students with 122 children, followed by elementary school students with 64 children and high school students with 60 children. Victims of violence including children were 79.2% of cases, while for adults it was 20.8%. Stress is thought to be a trigger for violence or bullying. Purpose: To determine the relationship between stress levels and bullying behavior in students. Method: This type of research is quantitative with a cross sectional approach analytical survey design. The total sample was 244 respondents taken from 2 SMPN 13 Bandar Lampung and SMPN 26 Bandar Lampung using purposive sampling technique. Univariate (frequency distribution) and bivariate data analysis using the chi square test.  Results: The results obtained from the level of stress that occurred at SMPN 13 Bandar Lampung, namely the level of mild stress was 44 (78.6%), and bullying behavior was low at 44 (56.4%). Meanwhile, at SMPN 26 Bandar Lampung the level of moderate stress was 22 (41.5%) and mild bullying behavior was 38 (88.4%). Chi square analysis test of the relationship between stress levels and the emergence of bullying behavior in students at SMP N 13 and 26 Bandar Lampung p-value 0.000 (< 0.05).  Conclusion: At SMP N 13 Bandar Lampung and SMP N 26 Bandar Lampung there was a relationship between stress levels and the emergence of bullying behavior with a p value of 0.000 (< 0.05).